Tepung temu hitam (Curcuma aeruginosa Roxb) dalam ransum memperbaiki produktifitas dan High Density Lipoprotein (HDL) serum itik pedaging Peking - A. A. Syaefudin; R. Murwani; Isroli Isroli (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The purpose of this research was todetermine the effect of Curcuma Aeruginosa Roxb.(C. Aeruginosa) powder addition on serum lipid (total cholesterol, LDL, HDL and triglycerides) and productivity of Peking duck. The material of the study were one hundred and twenty peking ducks aged 2 days old  with initial body weight ± 65 g. The experiment applied a completely randomized design with 5 treatments and 4 replications. Each replication consisted of 6 ducks. The treatment consisted of T0 = 0% C. Aeruginosa powder, T1 = 0.75% C. aeruginosa powder, T2 = 1% C. aeruginosa powder, T3= 1.25% C. aeruginosa powder and T4 = 1.5% C. aeruginosa powder. Comercial diet with 23% protein was given from day 2 to day 14 while day 15 ducks were given diet with 17.5% protein and 3029.7 kcal/kg metabolic energy. Curcuma aeruginosa powder was given on day 25 to day 57. Daily consumption was recorded and body weight was recorded once a week. Both samples were taken on day 57. The data were processed by ANOVA at P= 0.05. The results showed that addition of 1.25% C.Aeruginosa powder (T3) had the lowest consumption, higher body weight and body weight gain (BWG) with lowest feed conversion. Curcuma aeruginosa powder only affected significantly the HDL. All groups with C. aeruginosa addition showed higher HDL than control group. It can be concluded that addition of 1,25% (T3) C. Aeruginosa powder will produced the highest serum HDL, and provide better productivity. Keywords: C. aureginosa, Peking duck and serum lipid